Heterogeneity of Molecular Size of Factor Vlll/von Willebrand Factor in von Willebrand's Disease - Mikami, S; Takahashi, Y; Nishino, M; Okubo, Y; Fukui, H (Thrombosis and Haemostasis, 1981)
Patterns of VIIIR:AG in the plasma and its fractions, cryoprecipitate and cryosupernatant, from various types of von Willebrand’s disease (vWd) were observed by SDS 1.5% polyacrylamide gel electrophoresis - crossed immunoelectrophoresis (SDS PAGE - CIE).VIIIR:AG in normal cryoprecipitate showed several precipitin peaks which correspond to molecular weights ranging from 8 X 105 to 1 X 107 daltons and are similar to those in normal plasma. Normal cryosupernatant VIIIR: AG gave smaller molecular weights from 8 X 105 to 2 X 106 daltons.VIIIR:AG in the plasma and cryoprecipitate from 2 patients with classical vWd gave low precipitin peaks with molecular weights in normal range. VIIIR:AG from 2 patients with subgroup A variant which showed fast anodal migration on the conventional CIE, presented 3 peaks with molecular weights of 8 X 105 to 3 X 106 which are similar to those in normal cryosupernatant. VIIIR: AG from 2 patients with subgroup B variant which showed normal migration on the CIE, gave normal patterns through all fractions.
Keywords: von Willebrand’s disease; Factor VIII/von Willebrand factor; Molecular size; SDS polyacrylamide gel electrophoresis and crossed immunoelectrophoresis